Analisis Pengaruh Rotasi Kerja, Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan di Lembaga Keuangan Mikro Syariah - Taufikur Rahman; Siti Solikhah (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2016)
This study aims at investigating and analyzing the effect of job rotation(X1), motivation (X2), and job satisfaction (X3) toward employees’performance (Y). The population used in this study is all employee of BMTTaruna Sejahtera that consists of 172 people. The writer took 120 employeesas the sample of this research. The sampling technique used in this researchis a probability sampling technique, which is sampling technique thatprovides an equal opportunity for all members of the population to be selectedas the sample. The method used to collect the data is questionnaire. Toanalyze the data, the writer used a statistical test that includes t-test, F-test,the coefficient of determination (R2), and multiple regression tests. Theprocess of data analysis is using a means of IBM SPSS Statistics 23.Research finding shows that multiple linear regression equation Y is -12.335+ 0.364X1 + 0.296X2 + 0.235X3 + 0:05. Results of t-test show that thevariables of job rotation, motivation, and job satisfaction have positive andsignificant influence toward employees’ performance. In other words, thosevariables jointly influence employees’ performance. The coefficient ofdetermination (R2) is 0.883. It means that the contribution of independentvariables (job rotation, motivation and job satisfaction) has influence towarddependent variable (employees’ performance) amounted to 88.3%, whilethe rest is 11.7% influenced by other variables out of research model